Novel antimicrobial peptide with anticancer properties - Bakheit, Sheri Magdy Saleeb (AUC Knowledge Fountain, 2019)
Cancer is one of the highest leading causes of death at the mean time. There are multiple approaches developed for cancer treatment including chemotherapy, radiation, and hormonal therapy. Due to the toxicity and inefficiency of such approaches, small molecules drugs (<0.5 kDa) have emerged to overcome the limitations of current therapeutics. The great potential of peptide drugs emerged from their targeted selectivity and rare resistance acquirement. Previous research has been carried on a 37 residue antimicrobial peptide, and showed dose dependent cytotoxicity on early stage Hepatocellular carcinoma cell line (HepG2). This 37-mer peptide was retrieved from the AUC Red Sea metagenomics data generated during AUC/KAUST Red Sea microbiome project and modified to enhance its anti-cancer activity. The current research aims at characterizing the cytotoxicity of the 37-mer peptide drug on an advanced stage of hepatocellular carcinoma cell line (SNU449). The anticancer effect of the peptide is tested on cancer cells proliferation, morphology, viability and migration. The peptide cytotoxic effect on normal human erythrocytes is tested, defining its hemolytic activity. Finally, we investigated the peptide antimicrobial property on gram-positive and gram-negative bacterial strains. Peptide treatment caused a dose dependent cytotoxicity on SNU449, affecting cellular morphology. The treatment caused differential expression in some major cancer hallmarks involved in proliferation, migration, apoptosis and autophagy. This suggests that upon treatment, cells undergo programmed cell death pathway. The molecular machinery involving apoptosis and autophagy are responsible for peptide cytotoxic effect on the cells. Peptide also showed no considerable hemolytic activity on human red blood cells upon application. Finally, the antimicrobial effect of the peptide is established on both gram positive and gram negative bacterial strains.